RELATIONSHIP BETWEEN KNOWLEDGE AND COMMUNITY BEHAVIOR IN PRIMARY PREVENTION OF DHF IN VILLA MAKMUR, BEKASI - martina, siska evi (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2019)
In Indonesia, incidence of Dengue Hemorrhagic Fever (DHF) is increasing dramatically. The purpose of this study was to identify the relationship between knowledge level and community behavior in primary prevention of DHF in Villa Makmur, Bekasi. A cross sectional study was conducted with 144 respondents which is taking by purposive sampling technique. Questionarries thad had been compiled and modified was used as a tool in this study. The questionarries composed of the demographic characteristic and knowledge of DHF prevention. The study found that 72 respondents (50%) were 40-55 years old, 79 respondents were secondary level of education (54.9%), 131 respondents were employed (91%), 70 respondents had an enough knowledge about dengue (48.6%) and 78 respondents had a good behavior in prevention of DHF. There were a correlation between knowledge with primary prevention behavior of dengue fever with p value = 0.000 (p <0,05). Prevention of DHF is very important to reduceÂ the incidence of DHF. The community should be aware and improve the knowledge of DHF prevention.